Hurdling senescence: hur breaks braf-induced senescence in melanocytes and supports melanoma growth - Liebig, Janika; Kuphal, Silke; Boßerhoff, Anja Katrin (Cancers, 2020)
In addition to genetic changes, post-transcriptional events strongly contribute to the progression of malignant tumors. The RNA-binding protein HuR (ELAVL1) is able to bind and stabilize a large group of target mRNAs, which contain AU-rich elements (ARE) in their 3′- untranslated region. We found HuR to be upregulated in malignant melanoma in vitro and in vivo, significantly correlating with progression in vivo. Additionally, we could show that miR-194-5p can regulate HuR expression level. HuR knockdown in melanoma cells led to the suppression of proliferation and the induction of cellular senescence. Interestingly, HuR overexpression was sufficient to inhibit senescence in BRAFV600E -expressing melanocytes and to force their growth. Here, MITF (Microphthalmia-associated transcription factor), a key player in suppressing senescence and an ARE containing transcript, is positively regulated by HuR. Our results show for the first time that the overexpression of HuR is an important part of the regulatory pathway in the development of malignant melanoma and functions as a switch to overcome oncogene-induced senescence and to support melanoma formation. These newly defined alterations may provide possibilities for innovative therapeutic approaches.
CRIS-Team Scopus Importer:2020-06-02
Keywords: HuR; Malignant melanoma; Microphthalmia-associated transcription factor; MITF; Oncogene induced senescence

Importance of the RNA Binding Protein Hu-antigen R in malignant Melanoma - Liebig, Janika; Boßerhoff, Anja Katrin (2018)
EVALuna2:203602

MicroRNA-sequencing data analyzing melanoma development and progression - Linck, Lisa; Liebig, Janika; Voeller, Daniel; Eichner, Norbert; Lehmann, Gerhard; Meister, Gunter; Boßerhoff, Anja Katrin (Experimental and Molecular Pathology, 2018)
MicroRNAs (miRNAs) deregulated in melanoma are of growing importance in cancer research. We aimed to define the miRNAome of melanoma cell lines and primary melanocytes by RNA-Seq using identical cell lines as in a published miRNA expression study based on cDNA arrays. We identified 79 miRNAs, which are significantly deregulated during melanoma development. In addition, we could also determine 29 miRNAs being involved in melanoma progression. Interestingly, not all characterized miRNAs derived from cDNA array analyses of our and other groups could be found to be differentially expressed using RNA-Seq analyses, however, new miRNAs, formerly not associated with melanoma, were found to be strongly regulated.
EVALuna2:202902

MiRNAs in malignant melanoma - Mione, Maria; Liebig, Janika; Munoz, Leonel; Boßerhoff, Anja Katrin (Springer International Publishing, 2017)
MicroRNAs (miRNAs) represent a class of small noncoding RNAs, first described in the nematode Caenorhabditis elegans. In 1993, the labs of Victor Ambros (Lee et al. Cell 75:843-854, 1993) and Gary Ruvkun (Wightman et al. Cell 75:855-862, 1993) discovered lin-4, the first member of the inexorably growing family of miRNAs. Interestingly, it was not until the year 2000 that Reinhart and colleagues detected a second miRNA species-let-7 (Reinhart et al. Nature 2000;403:901-906). The finding that the sequence of let-7 was conserved in a large variety of Metazoens from Drosophila to humans (in contrast to lin-4, which is exclusively expressed in Caenorhabditis; Pasquinelli et al. Nature 408:86-89, 2000; Slack et al. Mol Cell 2000;5:659-669, 2000) fueled miRNA research and revealed that this class of molecules is involved in the regulation of gene expression at a posttranscriptional level in presumably every multicellular organism. To date, more than 1800 distinct miRNA species have been identified in the human genome (www.miRNA.org Kozomara and Griffiths-Jones 42(Database issue):D68-73, 2014). Those are estimated to regulate the expression of as much as 60 % of all human transcripts (Friedman et al. Genome Res 2009;19:92-105, 2009). MiRNAs are demonstrably involved in the physiological regulation of multiple cellular processes, such as proliferation, apoptosis, and differentiation. As a consequence, abnormalities in miRNA activity were found to contribute to the pathogenesis and progression of various types of human cancers (reviewed by Mirnezami et al. Eur J Surg Oncol 35:339-347, 2009; Visone and Croce Am J Pathol 2009;174:1131-1138, 2009), including malignant melanoma (reviewed by Mione and Bosserhoff Pigment Cell Melanoma Res 2015;28:340-354).
CRIS-Team Scopus Importer:2022-08-05